Intrinsic factors affecting ground beef color stability - Raines, Christopher Ryan (Kansas State University, 2008)
Three experiments were conducted to evaluate factors affecting ground beef color stability with the objectives: 1) To characterize color characteristics of different ground muscles from similarly fed and managed cows and steers; 2) To evaluate the contributions different muscles make to overall ground beef color stability; and 3) To determine if cow biological type (beef-type vs. dairy-type) affects ground beef color dynamics. In general, ground muscles from fed cows appeared darker and redder than ground muscles from steers. Chronological age did not affect ground beef color stability of muscles from fed cows. Use of steroid implants or [Beta]-agonists did not affect ground muscle color stability of fed steers or fed cows. Overall color stability varied more in muscle from steers than from fed cows. Fed cow muscles tended to have a greater proportion of saturated and mono-unsaturated fatty acids to poly-unsaturated fatty acids than fed steer muscles. Ground muscles from fed cows had better color stability properties than ground muscles from steer. When muscles of various color stability were blended to make ground beef and packaged in high-oxygen modified atmosphere (HiO[subscript]2 MAP), high color stability muscles (≥ 75%) in formulations maximizes display color life; however, inclusion of low color stability muscles (≥ 25%) in ground beef formulations had deleterious effects on ground beef color life. Ground semimembranosus (SM) from dairy cows exhibited darker initial color than ground SM from beef cows when packaged in HiO[subscript]2 MAP. However, ground SM from dairy cows was more color stable than ground SM from beef cows when packaged in HiO[subscript]2 MAP. Cow trim used as a fat source in ground beef formulations improved color stability compared to young beef trim when packaged in HiO[subscript]2 MAP. Isolating and managing muscle sources enable meat processors to better manage ground beef based upon intrinsic factors affecting ground beef color stability.
Keywords: ground beef; color stability; beef color; cow meat; Agriculture, Food Science and Technology (0359)